Food and feeding behaviour of Chestnut-tailed Starling, Sturnia malabarica at Jahangirnagar University Campus, Bangladesh - Rahman, Md Touhidur; Shoma, Shamia Farhana; Feeroz, Mohammed Mostafa; Hasan, Md Kamrul (Jahangirnagar University Journal of Biological Sciences, 2019)
Food and feeding behaviour of Chestnut-tailed Starling, Sturnia malabarica were studied at Jahangirnagar University Campus, Bangladesh, from August 2016 to March 2017. A total of 414 observations were made on the feeding maneuver and it was noted that they were omnivorous consuming 67.15% animal diet compared to 20.53%plant diet.They predominantly consumedinsect larvae(39%) followed by beetles (16%), nectar (14%), food wastes (12%), fruits (7%), dragonflies (7%), damselflies (3%), and worms (2%).Among the five types of feeding modes recorded,hang-upmode (37.92%) was major feeding technique in Chestnuttailed Starling while pecking mode (6.76%)was least used. Rain tree (Samanea saman) (33.76%) followed by White siris (Albizia procera) (30.55%) was recorded as the most utilized foraging plant while mostly preferred perching height by Chestnut-tailed Starling was 6-9m (44.9%) followed by 3-6m (31.6%). Jahangirnagar University J. Biol. Sci. 8(1): 17-23, 2019 (June)